Pediatric diaphyseal forearm fractures: epidemiology and treatment in an urban population during a 10-year period, with special attention to titanium elastic nailing and its complications. Issue 5 (September 2016) - Lyman, Amanda; Wenger, Daniel; Landin, Lennart
Abstract : This study aims to describe the epidemiology of pediatric diaphyseal forearm fractures in an urban population and the complications of titanium elastic nailing. The medical records of 456 consecutive fractures were reviewed. The annual incidence was 0.7/1000 children. Eighty-six (19%) fractures in 83 children were titanium elastic nailed. The complication rate was 24%. Dorsal entry to the radius was associated with extensor pollicis longus rupture and radial entry was associated with sensory nerve deficit in three cases each. Seventy-eight (94%) of the operated patients recovered completely. Titanium elastic nailing is effective, but associated with a high rate of complications, most of which resolve spontaneously. Abstract : Supplemental Digital Content is available in the text.